PENGARUH FAKTOR – FAKTOR CITRA MEREK (BRAND IMAGE) TERHADAP LOYALITAS PELANGGAN KANGOROO PREMIERE DI SAMARINDA - Adi Suroso, Rahmawati, Theresia Militina (EKONOMIA, 2016)
The aim of this study was to analyze the influence of brand image that consists Customer Satisfaction, Service Quality, Corporate Image, and Switching barrier to Customer loyalty on Kangoroo Premier transportation services in Samarinda and and knowing the dominant aspect that influence customer loyalty. Respondents in this study were 100 customers kangoroo Premier in Samarinda city for two months. Data collection method is by using a questionnaire with Likert scale measurement ranges 5. The theory used is the theory of marketing, brand image and loyalty.Analysis method using multiple linear regression. Hypothesis testing using F test and t test.The analysis showed that customer satisfaction, service quality, corporate image, and switching barriers significantly affect customer loyalty kangoroo Premier with F count = 56 151 and sig = 0.000> 0.05. Thus the hypothesis is accepted. The findings of this study indicate that service quality is the most dominant factor influencing the Premier kangoroo subscriber loyalty. While variable Customer Satisfaction, Corporate Image, and Switching barrier does not significantly affect customer loyalty.